STRATEGI PENGEMBANGAN USAHA TERNAK BEBEK PEDAGING DI TENGAH PANDEMI COVID 19 PADA KELOMPOK TANI MITRA TANI DESA SUKAMAJU KECAMATAN LABUAN KABUPATEN PANDEGLANG BANTEN - Sarajevo, Evo; Saleh, Khaerul; Sulaeni, Sulaeni (Jurnal Penyuluhan dan Pemberdayaan Masyarakat, 2023)
The purpose of the study was to determine the impact of identification and nalysis of internal and external factors that affect the broiler duck farming business in the Mitra Tani farmer group, Sukamaju Village, Labuan District, Pandeglang Regency, Banten. Designing a development strategy to develop a broiler duck farming business in the Mitra Tani farmer group, Sukamaju Village, Labuan District, Pandeglang Regency in the face of the Covid-19 pandemic. This research method uses IFE Matrix, EFE Matrix, and Swot Matrix. The results showed that the IFE matrix in the Mitra Tani farmer group in Sukamaju Village had a total score of 2.815 with the main strength having a business license with a score of 0.429. The main weakness of this farmer group is the manual/non-digital system with a score of 0.331. While the EFE matrix obtained a total score of 2.650 with the main opportunity for farmer groups is farmer group customer loyalty with a score of 0.463. The main threat faced by farmer groups is the emergence of similar business competitors with a score of 0.394. The results of the I-E matrix indicate that the position of the farmer group is in cell V, which is in a hold and maintain condition. Strategies that fit this quadrant are market penetration and product development. The results of the SWOT matrix obtained eight alternative strategies for developing Mitra Tani farmer groups in Sukamaju Village.